Knowledge management in transport services, a biliometric study (Research, Society and Development, 2020)
In the midst of the search for innovation in productive efficiency, organizations use several devices, so this study aims to identify how the fragment of the world scientific literature addresses the theme “Knowledge Management (GC)” in the context of “Transport Services” . For that, it uses bibliometrics as a methodological tool with the “Periódicos CAPES / MEC” portal as its research source. The results point to a balance in the dispersion of research with an emphasis on activities in public and private organizations, however the approaches used point in different directions. While research with public emphasis addresses the contributions of Knowledge Management (GC) to strategies for improving public transport and advancing actions on transparency, private investigations question elements of logistical aspects of transport in the production chain such as fleet management, cooperation between organizations, environmental sustainability and cost control. Regarding KM processes, there is a predilection in the debate on aspects related to the processes of acquisition, distribution and use of knowledge and aspects related to storage. In general, studies suggest the feasibility of using KM processes with significant contributions in different emphases and approaches. Among the limitations, the study pointed to a low index of research on the theme, indicating an avenue of knowledge to be followed.